Applications and prospects of biomaterials in diabetes management - Guan, Wenhe; Zhang, Liang (Frontiers in Bioengineering and Biotechnology, 2025)
Diabetes is a widespread metabolic disorder that presents considerable challenges in its management. Recent advancements in biomaterial research have shed light on innovative approaches for the treatment of diabetes. This review examines the role of biomaterials in diabetes diagnosis and treatment, as well as their application in managing diabetic wounds. By evaluating recent research developments alongside future obstacles, the review highlights the promising potential of biomaterials in diabetes care, underscoring their importance in enhancing patient outcomes and refining treatment methodologies.